2015
DOI: 10.1007/s12307-015-0176-8
|View full text |Cite
|
Sign up to set email alerts
|

SLUG and SOX9 Cooperatively Regulate Tumor Initiating Niche Factors in Breast Cancer

Abstract: Presence of tumor initiating cells and a proper niche is essential for metastatic colonization. SLUG and SOX9 transcription factors play essential roles in induction and maintenance of tumor initiating capacity in breast cancer cells. On the other hand, Tenascin-C and Periostin are crucial factors in metastatic niche that support tumor initiating capability in breast cancer. In this study, regulatory effect of SLUG and SOX9 transcription factors on the expression of Tenascin-C and Periostin was examined. SLUG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Breast cancer patients with high expression of SOX9 exhibited shorter overall survival than those with low expression (22,23). Numerous other studies have supported the importance of SOX9 in breast cancer occurrence and development through the regulation of multiple biological behaviors (24)(25)(26)(27)(28). In the current study, it was demonstrated that miR-511 targets SOX9 to inhibit the malignant progression of breast cancer via the PI3K/ Akt pathway.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Breast cancer patients with high expression of SOX9 exhibited shorter overall survival than those with low expression (22,23). Numerous other studies have supported the importance of SOX9 in breast cancer occurrence and development through the regulation of multiple biological behaviors (24)(25)(26)(27)(28). In the current study, it was demonstrated that miR-511 targets SOX9 to inhibit the malignant progression of breast cancer via the PI3K/ Akt pathway.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, it was aimed to determine the expression of miR-511 in breast cancer, test its role in malignant progression and explore downstream targets. SRY-box 9 (SOX9) was predicted as a potential target of miR-511 and was chosen for further investigation as this gene was previously reported to be upregulated in breast cancer and implicated in breast carcinogenesis and development (22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we constructed an miRNA–mRNA interaction network to obtain an overview of the putative function of the most differentially expressed miRNAs. This miRNA–mRNA interaction network suggested that differentially expressed miRNAs regulate tumor growth and metastasis‐related genes such as EGFR, MET, SOX9, SP1, PTEN, FOXO1 and ZEB1 . Of these target genes, SP1 and ZEB1 showed the most linkage with differentially expressed miRNAs.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, SOX9 is known to promote epithelial-mesenchymal transition (EMT) together with SLUG ( 32 , 33 ), one of the key transcriptional factors in EMT ( 34 ). When SOX9 and SLUG were overexpressed in breast cancer cells, they cooperatively facilitated EMT, resulting in elevated tumorigenesis and metastasis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%